Critical Discourse Network Analysis on Ferdy Sambo News in Online Media Using Agenda Setting Theory - Nuriyati Samatan; Nurhasanah Nurhasanah; Marwan Londol; Robingah Robingah; Salwa Fania (Ikatan Sarjana Komunikasi Indonesia, 2024)
This research aims to analyze the Critical Discourse Network Analysis of the news of the Ferdy Sambo Case on Online Media Portals through Agenda Setting Theory. The research employed a social networking analysis method that combines two elements of methods, namely qualitative content analysis and quantitative social network analysis, to analyze the news using Discourse Network Analysis (DNA) and network visualization using the Visone software application. Qualitative method was also employed to analyze the tendency of Kompas.com in framing the Ferdy Sambo case in the period of August 2022 to February 2023. The data analyzed covered 14 news reports. Based on Agenda Setting Theory, through Media Agenda analysis, Kompas.com emphasized the Ferdy Sambo case has become a cause for concern among the Indonesian people. This was reinforced by the convergence between mainstream mass media and social media; in terms of Public Agenda, Sambo's news, both through mainstream media such as Kompas.com and social media. The Ferdy Sambo case is very popular on social media; in terms of Policy Agenda. The death penalty meted out to Sambo is expected by the majority of Indonesian people. Meanwhile, the DNA test shows that there are 14 news articles with 80 statements from 12 actors. The 14 news articles are categorized into information, statements, decisions and laws, with 29 positive statements and 51 negative statements.This research used Mix Method to analyze the news of the Ferdy Sambo case using Agenda Setting Theory and Discourse Network Analysis (DNA).